Critical Review of Life Cycle Assessment of Local and Imported Food Commodities - Doffannoel Claudio Sihotang; Edberd E. Leopard; I Dewa Made Adi Kresna; Iqbal Zahid Abdullah Haris; Nurhayati (Penerbit Jurnal Indonesia, 2026)
This study aims to critically reviews Life Cycle Assessment (LCA) research in Indonesia’s food sector, focusing on both locally produced and imported commodities. Employing a critical review methodology, peer-reviewed articles and international reports published were analyzed for compliance with ISO 14040/44, data transparency, system boundary definitions, and methodological gaps. The results reveal substantial variability in environmental impacts: local rice and soybean value chains exhibit high methane emissions and fertilizer-related effects, whereas imported wheat, soybean, and beef accrue larger carbon footprints due to long-distance transport. Moreover, most studies adopt a cradle-to-gate scope with limited sensitivity or uncertainty analyses, which undermines result robustness. We conclude that standardizing LCA protocols, expanding primary data collection, and incorporating cradle-to-grave scopes and uncertainty analyses are vital to enhance the reliability of LCA for Indonesia’s sustainable food policy